Characterization of airborne emission of nanoparticles in the ceramic industry in Portugal - Esteves, H. (2021)
The objective of this study was to evaluate occupational exposure to nanoparticles during some tasks performed in different production processes of different ceramic industries in Portugal, to select the places of greatest occupational exposure through the analysis of the sampled data, to verify what is the pulmonary accumulation in these places, to identify the composition of the released nanoparticles, apply a Control Banding Tool and try to understand which companies require more risk control measures. The study was carried out in three different national ceramics production industries, one for sanitary ceramics production, another for porcelain crockery production, and finally another for the production of ornamental crockery (red paste). It is concluded that occupational exposure values to nanoparticles are high in all cases and that nanoparticles are very small in size (11.5 to 15.4 nm). Existing risk control measures are insufficient and verified risk levels are high (Risk Level 3 and 4). The chemical composition of the analyzed nanoparticles is similar regardless of the typology of the ceramic production plant and their chemical composition as a percentage of certain materials has a direct influence on crystallinity.